STUDYING OF SOME PHYSICAL AND CHEMICAL PROPERTIES OF SWAMPE WATER TO THE LOCAL AQUATIC PLANTS LEMNA spp. EXIT IN IT NATURALY - Thaiar Abrahem Kasem (Mesopotamia Journal of Agriculture)
This study was regionally for one of local aquatic plants called duckweed Lemna spp. And it's life in natural conditions for different regions water study of Baghdad within year seasons. The results of statistical analysis showed that there are significantly (p<0.05), differences in water properties in which the plant grows, such as temperature between 10-28ºC and pH between 6.80-8.35 and different concentrations of ammonia between 5.62-13.79 mg/l, nitrite between 0.0004-0.0038 mg/l, nitrate between 0.13-24.00 mg/l and phosphorus between 0.15-9.08 mg/l. and the concentration of water included various heavy elements like zinc between 0.07-0.70 mg/L and iron between 0.03-0.33 mg/L and lead 0.01-1.05 mg/L and Copper between 0.03-0.55 mg/L. The conciliation of the study is that duckweed plant can be obtained throughout the year depending on the suitable climatic conditions in our country at regions of the lowest levels of nutrients.